Brick production from industrial waste in Nakhon Si Thammarat Province - วันทอง, อุไรวรรณ (Progress in Applied Science and Technology, 2020)
Industries in Nakhon Si Thammarat Province produce a lot of cement waste during manufacturing of fiber cement roofs. Fiber glass waste and ceiling waste are expire that is very harmful for the environment. The main objective of this study is to use these cement waste for producing bricks. Normally stones, cement, sand, and water are used for brick production, but we would like to include cement waste along with these materials. This study aims to (1) produce bricks using several ratios to increase compressive strength, (2) to produce lightweight bricks for easy transportation and decrease Water Absorption, (3) to increase the capacity (thermal insulation) and (4) the cost effectiveness of cement waste bricks. The best ratio for brick production was stone (22) : sand (8) : water (4) : cement waste (3) : cement (2) for Fiber cement Roof waste, stone (23) : sand (8) : water (4): cement waste (4): cement (2) for ceiling waste and stone (22) : sand (8) : water (4) : cement waste (4) : cement (2) for Fiberglass waste (experimenting with the ratio of volume) because these bricks had the most compressive strength (average strength). The compressive strength of these bricks were 27.2% for Fiber cement Roof waste , 80.57 % for Fiber glass waste and 62.50 % for ceiling waste higher than local market bricks and compressive strength higher than standard bricks. The Spegific heat capacity of these bricks were 17.4 % for Fiber cement Roof waste , 16.76 % for Fiber glass waste and 15.14 %